Analysis of mitochondrial DNA sequences in childhood encephalomyopathies reveals new disease-associated variants - Wani, Aijaz A.; Ahanger, Sajad H.; Bapat, Sharmila A.; Rangrez, Ashraf Y.; Hingankar, Nitin; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh S. (Plos One, 2007)
Background. Mitochondrial encephalomyopathies are a heterogeneous group of clinical disorders generally caused due to mutations in either mitochondrial DNA (mtDNA) or nuclear genes encoding oxidative phosphorylation (OXPHOS). We analyzed the mtDNA sequences from a group of 23 pediatric patients with clinical and morphological features of mitochondrial encephalopathies and tried to establish a relationship of identified variants with the disease. Methodology/Principle Findings. Complete mitochondrial genomes were amplified by PCR and sequenced by automated DNA sequencing. Sequencing data was analyzed by SeqScape software and also confirmed by BLASTn program. Nucleotide sequences were compared with the revised Cambridge reference sequence (CRS) and sequences present in mitochondrial databases. The data obtained shows that a number of known and novel mtDNA variants were associated with the disease. Most of the non-synonymous variants were heteroplasmic (A4136G, A9194G and T11916A) suggesting their possibility of being pathogenic in nature. Some of the missense variants although homoplasmic were showing changes in highly conserved amino acids (T3394C, T3866C, and G9804A) and were previously identified with diseased conditions. Similarly, two other variants found in tRNA genes (G5783A and C8309T) could alter the secondary structure of Cys-tRNA and Lys-tRNA. Most of the variants occurred in single cases; however, a few occurred in more than one case (e. g. G5783A and A10149T). Conclusions and Significance. The mtDNA variants identified in this study could be the possible cause of mitochondrial encephalomyopathies with childhood onset in the patient group. Our study further strengthens the pathogenic score of known variants previously reported as provisionally pathogenic in mitochondrial diseases. The novel variants found in the present study can be potential candidates for further investigations to establish the relationship between their incidence and role in expressing the disease phenotype. This study will be useful in genetic diagnosis and counseling of mitochondrial diseases in India as well as worldwide.

Analysis of reactive oxygen species and antioxidant defenses in complex I deficient patients revealed a specific increase in superoxide dismutase activity - Wani, Aijaz A.; Rangrez, Ashraf Y.; Kumar, Himanshu; Bapat, Sharmila A.; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh (Free Radical Research, 2008)
The mechanism of free radical production by complex I deficiency is ill-defined, although it is of significant contemporary interest. This study studied the ROS production and antioxidant defenses in children with mitochondrial NADH dehydrogenase deficiency. ROS production has remained significantly elevated in patients compared to controls. The expression of all antioxidant enzymes significantly increased at mRNA level. However, the enzyme activities did not correlate with high mRNA or protein expression. Only the activity of superoxide dismutase (SOD) was found to correlate with higher mRNA expression in patient derived cell lines. The activities of the enzymes such as glutathione peroxidase (GPx), Catalase (CAT) and glutathione-S-transferase (GST) were significantly reduced in patients (p < 0.05 or p < 0.01). Glutathione reductase (GR) activity and intracellular glutathione (GSH) levels were not changed. Decreased enzyme activities could be due to post-translational or oxidative modification of ROS scavenging enzymes. The information on the status of ROS and marking the alteration of ROS scavenging enzymes in peripheral lymphocytes or lymphoblast cell lines will provide a better way to design antioxidant therapies for such disorders.
Keywords: antioxidant enzymes; mitochondrial complex I; mitochondrial myopathies; Reactive Oxygen Species (ROS)

Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

Molecular cloning, over expression, and activity studies of a peptidic HIV-1 protease inhibitor: designed synthetic gene to functional recombinant peptide - Vathipadiekal, Vinod; Umasankar, Perunthottathu K.; Patole, Milind S.; Rao, Mala (Peptides, 2010)
The aspartic protease inhibitor (ATBI) purified from a Bacillus sp. is a potent inhibitor of several proteases including recombinant HIV-1 protease, pepsin, and fungal aspartic protease. In this study, we report the cloning, and over expression of a synthetic gene coding for ATBI in Escherichia coli and establish a purification Protocol. The ATBI molecule consists of eleven amino acids and is peptidic in nature. We used the peptide sequence data of ATBI to synthesize complementary oligonucleotides, which were annealed and subsequently cloned in-frame with the gene for glutathione-S-transferase (GST). The expression of the resulting fusion protein was induced in E. coli BL21-A1 cells using arabinose. The recombinant peptide was Purified using a reduced glutathione column, and cleaved with Factor Xa to remove the GST tag. The resultant product was further purified to homogeneity using RP-HPLC. Mass spectroscopy analysis revealed that the purified peptide had a molecular weight of 1186 Da which matches the theoretical molecular weight of the amino acids present in the synthetic gene. The recombinant peptide was found to be active in vitro against HIV-1 protease, pepsin, and fungal aspartic protease. The protocol described in this study may be used to clone pharmaceutically important peptide molecules. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Gateway cloning; HIV-1 protease; inhibitor; Proteases; Synthetic gene